Lake sediment records of deglaciation and post-glacial paleoenvironmental conditions, northeast Pennsylvania, USA - Matthew S. Finkenbinder; Timothy P. Lane; Kathryn R. Adamson; Bruce P. Finney; Mark B. Abbott; Alistair J. Monteath; Adam Ianno; Cassandra N. Papp; Angus F. Fortune; Michael J. Delpais; Megan E. Novak; Angelica Y. Delgado Rodriguez; et al. (Quaternary Science Reviews, 2026)

Impact of pristine and UV-aged conventional and compostable plastic bags on water quality: Physicochemical alterations, additive leaching, and ecotoxicological effects - Stefano Carnati; Ula Rozman; Janja Novak; Mark Starin; Andrea Pozzi; Davide Spanu; Gabriela Kalčíková; Gilberto Binda (Journal of Hazardous Materials, 2026)

Additives in microplastics shape biofilm composition during aging and favour antibiotic-resistant microorganisms - Barbara Klun; Živa Zidar; Anja Klančnik; Mark Starin; Janja Novak; Ula Rozman; Nataša Čelan Korošin; Changhae Kim; Jinho Jung; Gabriela Kalčíková (Environmental Pollution, 2026)

Integrating approaches and regulations to address plastic pollution: Spotlighting nanosized particles - Sara Novak; Mark Morrison; Rudolf Reuther; Lesley Tobin de Fuentes; Veno Kononenko; Damjana Drobne (NanoImpact, 2026)

FracFeed : Global database of the fraction of feeding predators - Mark Novak; Paige Foust; Shannon Hennessey; Brian P. Tanis; Kyle E. Coblentz; Christopher Wolf; Leah M. Segui; Jeremy S. Henderson; Kurt E. Ingeman; Landon P. Falke; Tamara J. Layden; Daniel J. Gradison; et al. (Ecology, 2026)
The proportion of individuals that are found to have empty stomachs during a survey of a predator population's diet has been used as an indicator of the average individual's state of energy balance and of the degree to which its feeding rate (i.e., its functional response) is saturated with respect to prey availability. As such, the proportion of empty stomachs provides insights into the effects of prey on predators and vice versa, although it is typically unreported in deference to descriptions of the contents of the non‐empty stomachs. The FracFeed database is an ongoing compilation of the proportions of empty and non‐empty stomachs (for gut content surveys) and of feeding and not feeding individuals (for direct observation surveys) reported in publications of predator diet surveys. FracFeed contains data from 4920 diet surveys on 1507 taxa (>4.3 million individuals) spanning cnidarians, ctenophores, chaetognaths, birds, annelids, amphibians, arthropods, mammals, mollusks, reptiles, echinoderms, and fishes that were surveyed in terrestrial, marine, and freshwater ecosystems across the globe over more than 135 years (1887–2023). For most surveys, covariate data include information on the spatial and temporal extent of the diet survey, its central geographical coordinates, the method by which the survey was performed (lethal gut contents, lavage, or direct observation), as well as each predator's standardized taxonomic name and identifier in the Open Tree of Life, its body mass (compiled mostly from independent compilations and additional publications), and its apparent diet's taxonomic richness and resolution. We appeal to more researchers who perform diet surveys to report on the number of empty stomachs they find and encourage additional contributions to the database—particularly from underrepresented geographic regions (e.g., North and Central Asia, North and Central Africa)—to help grow its scope and utility. The database is provided under a CC‐BY‐NC‐S4 4.0 license. Users are requested to cite this data paper when using the data.

Biofilm formation on polyethylene and polylactic acid microplastics in freshwater: Influence of environmental factors - Barbara Klun; Mark Starin; Janja Novak; Ula Putar; Nataša Čelan Korošin; Gilberto Binda; Gabriela Kalčíková (Journal of Environmental Chemical Engineering, 2025)

Simple, Universal Rules Predict Trophic Interaction Strengths - Kyle E. Coblentz; Mark Novak; John P. DeLong (Ecology Letters, 2025)
Many drivers of ecological systems exhibit regular scaling relationships, yet the mechanisms explaining these relationships are often unknown. Trophic interaction strengths are no exception, exhibiting scaling relationships with predator and prey traits that lack evolutionary explanations. We propose two rules to explain the scaling of trophic interaction strengths through the relationship between a predator's feeding rate and its prey's density—the so‐called predator functional response. First, functional responses allow predators to meet their energetic demands when prey are rare. Second, functional responses approach their maxima near the highest prey densities predators experience. We show that equations derived from these rules predict functional response parameters across over 2100 functional response experiments and make additional predictions such as their allometric scaling. The two rules thereby offer a potential ultimate explanation for the determinants of trophic interaction strengths, revealing ecologically realised constraints to the complex, adaptive nature of functional response evolution.

Understanding microplastic retention in surface flow constructed wetlands: The impact of aquatic macrophytes - Martina Miloloža; Ula Putar; Mark Starin; Janja Novak; Gabriela Kalčíková (Journal of Environmental Chemical Engineering, 2025)

Body Mass–Biomass Scaling Modulates Species Keystone‐Ness to Press Perturbations - Xiaoxiao Li; Wei Yang; Mark Novak; Lei Zhao; Peter C. de Ruiter; Zhifeng Yang; Christian Guill (Ecology Letters, 2025)
Identifying species with disproportionate effects on other species under press perturbations is essential, yet how species traits and community context drive their ‘keystone‐ness’ remain unclear. We quantified keystone‐ness as linearly approximated per capita net effect derived from normalised inverse community matrices and as non‐linear per capita community biomass change from simulated perturbations in food webs with varying biomass structure. In bottom‐heavy webs (negative relationship between species' body mass and their biomass within the web), larger species at higher trophic levels tended to be keystone species, whereas in top‐heavy webs (positive body mass to biomass relationship), the opposite was true and the relationships between species' energetic traits and keystone‐ness were weakened or reversed compared to bottom‐heavy webs. Linear approximations aligned well with non‐linear responses in bottom‐heavy webs, but were less consistent in top‐heavy webs. These findings highlight the importance of community context in shaping species' keystone‐ness and informing effective conservation actions.

The CRISM investigation in Mars orbit: Overview, history, and delivered data products - Frank P. Seelos; Kimberly D. Seelos; Scott L. Murchie; M. Alexandra Matiella Novak; Christopher D. Hash; M. Frank Morgan; Raymond E. Arvidson; John Aiello; Jean-Pierre Bibring; Janice L. Bishop; John D. Boldt; Ariana R. Boyd; et al. (Icarus, 2024)

ATP breakdown in plasma of children limits the antimicrobial effectiveness of their neutrophils - Carola Ledderose; Eleftheria-Angeliki Valsami; Margaret Newhams; Mark-Josef Elevado; Tanya Novak; Adrienne G. Randolph; Wolfgang G. Junger (Purinergic Signalling, 2023)

Geochemical and physical variability of Icelandic tephra fields and glaciovolcanic sandur to inform spatial sampling in Mars biosignature searches - Morgan L. Cable; Alexander M. Sessa; Erika Rader; Anna C. Simpson; Ashley M. Hanna; Diana M. Gentry; Scot M. Sutton; Elena S. Amador; Carlie Novak; Chloe LeCates; Mark Helmlinger; Amanda M. Stockton; et al. (Planetary and Space Science, 2023)

High variation in handling times confers 35‐year stability to predator feeding rates despite community change - Mark Novak (Ecology, 2023)
Historical resurveys of ecological communities are important for placing the structure of modern ecosystems in context. Rarely, however, are snapshot surveys alone sufficient for providing direct insight into the rates of the ecological processes underlying community functioning, either now or in the past. In this study, I used a statistically reasoned observational approach to estimate the feeding rates of a New Zealand intertidal predator, Haustrum haustorium , using diet surveys performed at several sites by Robert Paine in 1968–1969 and by me in 2004. Comparisons between time periods reveal a remarkable consistency in the predator's prey‐specific feeding rates, which contrasts with the changes I observed in prey abundances, the predator's body‐size distribution, and the prey's proportional contributions to the predator's apparent diet. Although these and additional changes in the predator's per‐capita attack rates seem to show adaptive changes in its prey preferences, they do not. Rather, feeding‐rate stability is an inherently statistical consequence of the predator's high among‐prey variation in handling times which determine the length of time that feeding events will remain detectable to observers performing diet surveys. Though understudied, similarly high among‐prey variation in handling (or digestion) times is evident in many predator species throughout the animal kingdom. The resultant disconnect between a predator's apparent diet and its actual feeding rates suggests that much of the temporal, biogeographic, and seemingly context‐dependent variation that is often perceived in community structure, predator diets, and food‐web topology may be of less functional consequence than assumed. Qualitative changes in ecological pattern need not represent qualitative changes in ecological process.

Predator feeding rates may often be unsaturated under typical prey densities - Kyle E. Coblentz; Mark Novak; John P. DeLong (Ecology Letters, 2023)
Predator feeding rates (described by their functional response) must saturate at high prey densities. Although thousands of manipulative functional response experiments show feeding rate saturation at high densities under controlled conditions, it remains unclear how saturated feeding rates are at natural prey densities. The general degree of feeding rate saturation has important implications for the processes determining feeding rates and how they respond to changes in prey density. To address this, we linked two databases—one of functional response parameters and one on mass–abundance scaling—through prey mass to calculate a feeding rate saturation index. We find that: (1) feeding rates may commonly be unsaturated and (2) the degree of saturation varies with predator and prey taxonomic identities and body sizes, habitat, interaction dimension and temperature. These results reshape our conceptualisation of predator–prey interactions in nature and suggest new research on the ecological and evolutionary implications of unsaturated feeding rates.

Effects of predator novelty on intraguild predation communities with adaptive prey defense - Kurt E. Ingeman; Mark Novak (Theoretical Ecology, 2022)
Understanding coexistence within community modules such as intraguild predation (IGP), where an omnivore both preys on and competes with an intermediate consumer for a shared resource, has provided insight into the mechanisms that promote the persistence of complex food webs. Adaptive, predator-specific defense has been shown theoretically to enhance coexistence of IGP communities when employed by shared prey. Yet to date, all such theory has assumed that prey have an accurate perception of predation risk and appropriate antipredator responses, assumptions that may not be justified when considering a novel predator. We therefore consider the effects of an introduced predator on IGP coexistence, describing two invasion scenarios: suboptimal defense, whereby a similar invader elicits an ineffective antipredator response; and naïveté toward an unfamiliar invader, for which prey fail to accurately estimate predation risk. We examine predictions for native predator persistence across gradients of enrichment and defense costs. The model predicts that predator novelty can weaken the effect of adaptive defense, causing exclusion of native predators that would persist in the absence of novelty and inducing unstable dynamics in previously stable regions of parameter space. Coexistence is predicted to be more sensitive to the effects of suboptimal defense than to naïveté, and differentially leads to the exclusion of native predators in highly productive environments and when defense costs are low. Moderate novelty of the omnivore can increase resource density via a trophic cascade, while consumer novelty can either lead to omnivore exclusion or facilitate three-species coexistence by providing a subsidy to the otherwise excluded native omnivore. Our analyses suggest that models of adaptive defense are sensitive to assumptions regarding predator–prey eco-evolutionary experience and that predator novelty has significant implications for food web dynamics.

Hidden layers of density dependence in consumer feeding rates - Daniel B. Stouffer; Mark Novak (Ecology Letters, 2021)
Functional responses relate a consumer's feeding rates to variation in its abiotic and biotic environment, providing insight into consumer behaviour and fitness, and underpinning population and food‐web dynamics. Despite their broad relevance and long‐standing history, we show here that the types of density dependence found in classic resource‐ and consumer‐dependent functional‐response models equate to strong and often untenable assumptions about the independence of processes underlying feeding rates. We first demonstrate mathematically how to quantify non‐independence between feeding and consumer interference and between feeding on multiple resources. We then analyse two large collections of functional‐response data sets to show that non‐independence is pervasive and borne out in previously hidden forms of density dependence. Our results provide a new lens through which to view variation in consumer feeding rates and disentangle the biological underpinnings of species interactions in multi‐species contexts.

Systematic bias in studies of consumer functional responses - Mark Novak; Daniel B. Stouffer (Ecology Letters, 2021)
Functional responses are a cornerstone to our understanding of consumer–resource interactions, so how to best describe them using models has been actively debated. Here we focus on the consumer dependence of functional responses to evidence systematic bias in the statistical comparison of functional‐response models and the estimation of their parameters. Both forms of bias are universal to nonlinear models (irrespective of consumer dependence) and are rooted in a lack of sufficient replication. Using a large compilation of published datasets, we show that – due to the prevalence of low sample size studies – neither the overall frequency by which alternative models achieve top rank nor the frequency distribution of parameter point estimates should be treated as providing insight into the general form or central tendency of consumer interference. We call for renewed clarity in the varied purposes that motivate the study of functional responses, purposes that can compete with each other in dictating the design, analysis and interpretation of functional‐response experiments.

Food‐web interaction strength distributions are conserved by greater variation between than within predator–prey pairs - Daniel L. Preston; Landon P. Falke; Jeremy S. Henderson; Mark Novak (Ecology, 2019)
Species interactions in food webs are usually recognized as dynamic, varying across species, space, and time because of biotic and abiotic drivers. Yet food webs also show emergent properties that appear consistent, such as a skewed frequency distribution of interaction strengths (many weak, few strong). Reconciling these two properties requires an understanding of the variation in pairwise interaction strengths and its underlying mechanisms. We estimated stream sculpin feeding rates in three seasons at nine sites in Oregon to examine variation in trophic interaction strengths both across and within predator–prey pairs. Predator and prey densities, prey body mass, and abiotic factors were considered as putative drivers of within‐pair variation over space and time. We hypothesized that consistently skewed interaction strength distributions could result if individual interaction strengths show relatively little variation, or alternatively, if interaction strengths vary but shift in ways that conserve their overall frequency distribution. Feeding rate distributions remained consistently and positively skewed across all sites and seasons. The mean coefficient of variation in feeding rates within each of 25 focal species pairs across surveys was less than half the mean coefficient of variation seen across species pairs within a survey. The rank order of feeding rates also remained conserved across streams, seasons and individual surveys. On average, feeding rates on each prey taxon nonetheless varied by a hundredfold, with some feeding rates showing more variation in space and others in time. In general, feeding rates increased with prey density and decreased with high stream flows and low water temperatures, although for nearly half of all species pairs, factors other than prey density explained the most variation. Our findings show that although individual interaction strengths exhibit considerable variation in space and time, they can nonetheless remain relatively consistent, and thus predictable, compared to the even larger variation that occurs across species pairs. These results highlight how the ecological scale of inference can strongly shape conclusions about interaction strength consistency and help reconcile how the skewed nature of interaction strength distributions can persist in highly dynamic food webs.

Planning for Change: Assessing the Potential Role of Marine Protected Areas and Fisheries Management Approaches for Resilience Management in a Changing Ocean - Kristy Kroeker; Mark Carr; Peter Raimondi; Jennifer Caselle; Libe Washburn; Stephen Palumbi; John Barth; Francis Chan; Bruce Menge; Kristen Milligan; Mark Novak; J. Wilson White (Oceanography, 2019)

Community Responses to Climate-Related Variability and Disease: The Critical Importance of Long-Term Research - Bruce Menge; Jennifer Caselle; John Barth; Carol Blanchette; Mark Carr; Francis Chan; Sarah Gravem; Tarik Gouhier; Jane Lubchenco; Margaret McManus; Kristen Milligan; Mark Novak; et al. (Oceanography, 2019)

Integrating Coastal Oceanic and Benthic Ecological Approaches for Understanding Large-Scale Meta-Ecosystem Dynamics - Bruce Menge; Jennifer Caselle; Kristen Milligan; Sarah Gravem; Tarik Gouhier; J. Wilson White; John Barth; Carol Blanchette; Mark Carr; Francis Chan; Jane Lubchenco; Margaret McManus; et al. (Oceanography, 2019)

PISCO: Advances Made Through the Formation of a Large-Scale, Long-Term Consortium for Integrated Understanding of Coastal Ecosystem Dynamics - Bruce Menge; Kristen Milligan; Jennifer Caselle; John Barth; Carol Blanchette; Mark Carr; Francis Chan; Robert Cowen; Mark Denny; Steven Gaines; Gretchen Hofmann; Kristy Kroeker; et al. (Oceanography, 2019)

What drives interaction strengths in complex food webs? A test with feeding rates of a generalist stream predator - Daniel L. Preston; Jeremy S. Henderson; Landon P. Falke; Leah M. Segui; Tamara J. Layden; Mark Novak (Ecology, 2018)
Describing the mechanisms that drive variation in species interaction strengths is central to understanding, predicting, and managing community dynamics. Multiple factors have been linked to trophic interaction strength variation, including species densities, species traits, and abiotic factors. Yet most empirical tests of the relative roles of multiple mechanisms that drive variation have been limited to simplified experiments that may diverge from the dynamics of natural food webs. Here, we used a field‐based observational approach to quantify the roles of prey density, predator density, predator‐prey body‐mass ratios, prey identity, and abiotic factors in driving variation in feeding rates of reticulate sculpin ( Cottus perplexus ). We combined data on over 6,000 predator‐prey observations with prey identification time functions to estimate 289 prey‐specific feeding rates at nine stream sites in Oregon. Feeding rates on 57 prey types showed an approximately log‐normal distribution, with few strong and many weak interactions. Model selection indicated that prey density, followed by prey identity, were the two most important predictors of prey‐specific sculpin feeding rates. Feeding rates showed a positive relationship with prey taxon densities that was inconsistent with predator saturation predicted by current functional response models. Feeding rates also exhibited four orders‐of‐magnitude in variation across prey taxonomic orders, with the lowest feeding rates observed on prey with significant anti‐predator defenses. Body‐mass ratios were the third most important predictor variable, showing a hump‐shaped relationship with the highest feeding rates at intermediate ratios. Sculpin density was negatively correlated with feeding rates, consistent with the presence of intraspecific predator interference. Our results highlight how multiple co‐occurring drivers shape trophic interactions in nature and underscore ways in which simplified experiments or reliance on scaling laws alone may lead to biased inferences about the structure and dynamics of species‐rich food webs.

Bayesian characterization of uncertainty in species interaction strengths - Christopher Wolf; Mark Novak; Alix I. Gitelman (Oecologia, 2017)

Quantifying predator dependence in the functional response of generalist predators - Mark Novak; Christopher Wolf; Kyle E. Coblentz; Isaac D. Shepard (Ecology Letters, 2017)
A long‐standing debate concerns how functional responses are best described. Theory suggests that ratio dependence is consistent with many food web patterns left unexplained by the simplest prey‐dependent models. However, for logistical reasons, ratio dependence and predator dependence more generally have seen infrequent empirical evaluation and then only so in specialist predators, which are rare in nature. Here we develop an approach to simultaneously estimate the prey‐specific attack rates and predator‐specific interference (facilitation) rates of predators interacting with arbitrary numbers of prey and predator species in the field. We apply the approach to surveys and experiments involving two intertidal whelks and their full suite of potential prey. Our study provides strong evidence for predator dependence that is poorly described by the ratio dependent model over manipulated and natural ranges of species abundances. It also indicates how, for generalist predators, even the qualitative nature of predator dependence can be prey‐specific.

The application of Bayesian hierarchical models to quantify individual diet specialization - Kyle E. Coblentz; Adam E. Rosenblatt; Mark Novak (Ecology, 2017)
Intraspecific variation in ecologically relevant traits is widespread. In generalist predators in particular, individual diet specialization is likely to have important consequences for food webs. Understanding individual diet specialization empirically requires the ability to quantify individual diet preferences accurately. Here we compare the currently used frequentist maximum likelihood approach, which infers individual preferences using the observed prey proportions to Bayesian hierarchical models that instead estimate these proportions. Using simulated and empirical data, we find that the approach of using observed prey proportions consistently overestimates diet specialization relative to the Bayesian hierarchical approach when the number of prey observations per individual is low or the number of prey observations vary among individuals, two common features of empirical data. Furthermore, the Bayesian hierarchical approach permits the estimation of point estimates for both prey proportions and their variability within and among levels of organization (i.e., individuals, experimental treatments, populations), while also characterizing the uncertainty of these estimates in ways inaccessible to frequentist methods. The Bayesian hierarchical approach provides a useful framework for improving the quantification and understanding of intraspecific variation in diet specialization studies.

Timescales alter the inferred strength and temporal consistency of intraspecific diet specialization - Mark Novak; M. Tim Tinker (Oecologia, 2015)

Designing relevant biochars as soil amendments using lignocellulosic-based and manure-based feedstocks - Jeffrey M. Novak; Keri B. Cantrell; Donald W. Watts; Warren J. Busscher; Mark G. Johnson (Journal of Soils and Sediments, 2014)

A multi‐decade time series of kelp forest community structure at San Nicolas Island, California (USA) - Michael C. Kenner; James A. Estes; M. Tim Tinker; James L. Bodkin; Robert K. Cowen; Christopher Harrold; Brian B. Hatfield; Mark Novak; Andrew Rassweiler; Daniel C. Reed (Ecology, 2013)
San Nicolas Island is surrounded by broad areas of shallow subtidal habitat, characterized by dynamic kelp forest communities that undergo dramatic and abrupt shifts in community composition. Although these reefs are fished, the physical isolation of the island means that they receive less impact from human activities than most reefs in Southern California, making San Nicolas an ideal place to evaluate alternative theories about the dynamics of these communities. Here we present monitoring data from seven sampling stations surrounding the island, including data on fish, invertebrate, and algal abundance. These data are unusual among subtidal monitoring data sets in that they combine relatively frequent sampling (twice per year) with an exceptionally long time series (since 1980). Other outstanding qualities of the data set are the high taxonomic resolution captured and the monitoring of permanent quadrats and swaths where the history of the community structure at specific locations has been recorded through time. Finally, the data span a period that includes two of the strongest ENSO events on record, a major shift in the Pacific decadal oscillation, and the reintroduction of sea otters to the island in 1987 after at least 150 years of absence. These events provide opportunities to evaluate the effects of bottom‐up forcing, top‐down control, and physical disturbance on shallow rocky reef communities.

Structure and mechanism of diet specialisation: testing models of individual variation in resource use with sea otters - M. Tim Tinker; Paulo R. Guimarães; Mark Novak; Flavia Maria Darcie Marquitti; James L. Bodkin; Michelle Staedler; Gena Bentall; James A. Estes (Ecology Letters, 2012)
Ecology Letters (2012) 15 : 475–483 Abstract Studies of consumer‐resource interactions suggest that individual diet specialisation is empirically widespread and theoretically important to the organisation and dynamics of populations and communities. We used weighted networks to analyze the resource use by sea otters, testing three alternative models for how individual diet specialisation may arise. As expected, individual specialisation was absent when otter density was low, but increased at high‐otter density. A high‐density emergence of nested resource‐use networks was consistent with the model assuming individuals share preference ranks. However, a density‐dependent emergence of a non‐nested modular network for ‘core’ resources was more consistent with the ‘competitive refuge’ model. Individuals from different diet modules showed predictable variation in rank‐order prey preferences and handling times of core resources, further supporting the competitive refuge model. Our findings support a hierarchical organisation of diet specialisation and suggest individual use of core and marginal resources may be driven by different selective pressures.

Nestedness patterns and the dual nature of community reassembly in C alifornia streams: a multivariate permutation‐based approach - Mark Novak; Jonathan W. Moore; Robert A. Leidy (Global Change Biology, 2011)
Many factors contribute to the nonrandom processes of extinctions and invasions that are changing the structure of ecological communities worldwide. These factors include the attributes of the species, their abiotic environment, and the interactions and feedbacks between them. The relative importance of these factors has been difficult to quantify. We used nested subset theory and a novel permutation‐based extension of gradient analysis to disentangle the direct and indirect pathways by which these factors affect the metacommunity structure of freshwater fishes inhabiting the streams tributary to the S an F rancisco B ay. Our analyses provide quantitative measures of how species and stream attributes may influence extinction vulnerability and invasion risk, highlight the need for considering the multiple interacting drivers of community change concurrently, and indicate that the ongoing disassembly and assembly of B ay A rea freshwater fish communities are not fully symmetric processes. Fish communities are being taken apart and put back together in only partially analogous trajectories of extinction and invasion for which no single explanatory hypothesis is sufficient. Our study thereby contributes to the forecasting of continued community change and its effects on the functioning of freshwater ecosystems.

Generalized modeling of ecological population dynamics - Justin D. Yeakel; Dirk Stiefs; Mark Novak; Thilo Gross (Theoretical Ecology, 2011)

Estimating interaction strengths in nature: experimental support for an observational approach - Mark Novak (Ecology, 2010)
The complexity of food webs poses a significant hurdle for our growing understanding of the structure and dynamics of ecological communities. Empirical methods that measure the per capita strengths of trophic species interactions offer a means to identify keystone species and bridge mathematical models and data to synthesize our knowledge of population dynamics and predator feeding behaviors. Many such methods have been proposed, but few have seen independent validation of their estimates or underlying assumptions. This is particularly so with respect to the nonlinear functional responses by which predators often respond to their prey. Here I describe an empirical test of a recently proposed observational method for estimating the nonlinear strength of predator–prey interactions in the field. By applying the method to two populations of a predatory intertidal whelk, Haustrum scobina , I estimated its per capita attack rates on all nine of its observed prey species. These spanned two orders of magnitude in per capita strength. Concurrent experimental manipulations of the two predator populations provided population time series for the response of a mussel prey species , Xenostrobus pulex . I obtained independent interaction strength estimates for this focal interaction by fitting a sequence of hypothesized predator–prey models to these time series. Overall, site‐specific models assuming linear functional responses performed better than all others. A direct comparison of the attack‐rate estimates from the observational method with those of the best‐performing nonlinear model nevertheless revealed high concordance between the two methods. The results of this study therefore support the use of the observational method in larger and more complex food webs and suggest that trophic interactions in the range of mean prey densities observed in nature are approximately linear.